2018
DOI: 10.1111/tbj.13066
|View full text |Cite
|
Sign up to set email alerts
|

Timing of radiation therapy in nipple-sparing mastectomy influences outcomes and patient-reported quality of life

Abstract: The aim of this study is to assess the complication profile and impact on patient-reported quality of life in those undergoing nipple-sparing mastectomy (NSM) with immediate breast reconstruction and subsequent prosthetic reconstruction in patients with prior breast radiation therapy (pRT) vs those receiving adjuvant post-mastectomy radiation therapy (PMRT). An IRB-approved, retrospective analysis was performed from 2002 to 2014 to identify NSM patients that underwent pRT or PMRT. A 22-item Likert scale questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…In an attempt to characterize the effects of radiation timing in NSM patients, Sosin et al published a retrospective study of 40 NSM patients with a history of radiation in 2018. 48 Nineteen patients with radiation therapy prior to mastectomy had a mean time of 5 years between radiation completion and NSM, and 21 patients who underwent postmastectomy therapy had a mean time of 24.6 weeks from NSM to first radiation dose. Following NSM, all patients underwent immediate tissue expander reconstruction and subsequent implant placement.…”
Section: Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…In an attempt to characterize the effects of radiation timing in NSM patients, Sosin et al published a retrospective study of 40 NSM patients with a history of radiation in 2018. 48 Nineteen patients with radiation therapy prior to mastectomy had a mean time of 5 years between radiation completion and NSM, and 21 patients who underwent postmastectomy therapy had a mean time of 24.6 weeks from NSM to first radiation dose. Following NSM, all patients underwent immediate tissue expander reconstruction and subsequent implant placement.…”
Section: Radiationmentioning
confidence: 99%
“…They concluded that NSM patients are less likely to have complications, require intraoperative interventions, and experience nipple necrosis when radiation is delivered prior to mastectomy compared with postoperatively. 48 Reisch et al examined the association of post-mastectomy radiation on outcomes following NSM with immediate prosthetic or delayed-immediate expander-autologous reconstruction. 18 Amongst 605 procedures after NSM, 43 received preoperative radiation and 45 received post-mastectomy radiation.…”
Section: Radiationmentioning
confidence: 99%
“…En el estudio publicado recientemente por Sosin et al 13 se analizan tanto complicaciones precoces como secuelas y necesidad de cirugía de revisió n en las 2 cohortes de pacientes. En dicho estudio tanto la tasa de complicaciones preoperatorias precoces como el porcentaje de secuelas que requieren reintervenciones despué s del primer mes es superior en la cohorte de pacientes que recibe radioterapia adyuvante (33,3% vs. 26,3% y 28,6% vs. 10,5%, respectivamente).…”
Section: Discusió Nunclassified
“…The surgical treatment of breast cancer has undergone a paradigm shift from lifesaving surgery to balancing the consideration of aesthetics and oncologic outcomes [12]. Skin-sparing mastectomy (SSM) has become popular for the treatment of oncologic breast surgery, since it ensures better patient satisfaction and quality of life and exhibits similar oncologic outcomes to conventional mastectomy [34].…”
Section: Introductionmentioning
confidence: 99%